Cross assessment of erosive processes with methodologies for quantifying soil loss - Giovanini Junior, Nelson [UNESP]; Lima, César Gustavo da Rocha [UNESP]; Carvalho, Mariana Barbosa de [UNESP]; Lollo, José Augusto de [UNESP] (Revista Brasileira de Geografia Fisica, 2022)
The erosive processes that take place across the globe are the cause and intensifier of several environmental problems. These can occur naturally-shaping the terrestrial structure-as well as in an anthropogenic way through harmful interventions to the environment. There are several methodologies to predict the intensity of soil loss in a region, providing data of local problems regarding the occurrence of erosion. In this study, three different methodologies are evaluated: natural vulnerability to erosion, USLE and AHP together with the support of a geographic information system environment, to determine the efficiency of each of these methods in the Hydrographic Basin of Córrego do Engano, São Paulo, Brazil. For the evaluation of each method, a cross-reference was conducted with real erosive process found in the study area using satellite images. It was found that USLE and AHP had the best results, with the local slope working as an important factor in the calculations.
Avaliação cruzada de processos erosivos com metodologias para quantificar a perda de solo
Keywords: Erosion; Erosion Prediction; GIS; Soil Management; USLE